Change-Ability for a World in Flux. (December 2022) - Rietveld, Erik
This article aims to sketch a new integrative perspective on what I call change-ability. I define change-ability as skilled ways of coordinating with a rapidly changing world. Many urgent societal challenges – from climate change to obesity, from the mass extinction of species to fraying social cohesion – require people to collectively change everyday patterns of behaviour they take for granted. The key insight I start from is that to durably change undesirable patterns of behaviour, we could start by changing the affordances the environment offers – the possibilities for action offered to us by the living environment. The aim of this article is to sketch an integrative conceptual framework for understanding change-ability in terms in terms of a dynamical 'brain ↔ body ↔ community ↔ landscape of affordances' system. This Change-Ability Conceptual Framework starts from the idea that individuals and communities are situated in the same rich landscape of affordances and suggests that making communities more change-able entails transforming the material 'grooves' that have formed in this landscape of affordances.